2012
DOI: 10.1097/ta.0b013e31824b1764
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hemodynamic measurements from invasive and noninvasive monitoring during early resuscitation

Abstract: Measurements of CO and SV were moderately strong in correlation and agreement which may suggest PAC measurements overestimate actual values. The significance of tricuspid regurgitation and mitral regurgitation during early resuscitation is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…CUS performed by intensivists has played an important role in ICUs because it is a noninvasive test that provides useful hemodynamic information [1][2][3][4][5][6][7][8]. Furthermore, problem-focused US can help identify specific problems e.g., fluid collection, DVT, biliary tract diseases, and urinary tract obstruction, which are common in surgical patients as seen in the present study [13,14].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…CUS performed by intensivists has played an important role in ICUs because it is a noninvasive test that provides useful hemodynamic information [1][2][3][4][5][6][7][8]. Furthermore, problem-focused US can help identify specific problems e.g., fluid collection, DVT, biliary tract diseases, and urinary tract obstruction, which are common in surgical patients as seen in the present study [13,14].…”
Section: Discussionmentioning
confidence: 87%
“…Ultrasonography (US) has become an essential tool in almost every subdivision of medical practice including critical care medicine. Various applications of US have been used in ICUs, for instance, monitoring of hemodynamic parameters such as intravascular volume (preload) and cardiac contractility [1][2][3][4][5][6][7][8]. Despite the fact that US has some inherent limitations and is largely operator dependent, it enables clinicians to rapidly assess unstable patients by the bedside and is relatively inexpensive.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiac output can reliably be measured with echocardiography using Doppler measurements of left ventricular outflow tract [8][9][10]. In trauma patients, cardiac output measurements from pulmonary artery catheter and transthoracic echocardiography were significantly related and agreed with moderate strength [9].…”
Section: Echocardiography In Shockmentioning
confidence: 83%
“…Whether echocardiography can replace TD method in CO measurement remains controversial. Some studies [13–15] have revealed that echocardiography is a rapid, accurate, and noninvasive monitoring technology suitable for patients in ICU. Although differences were observed, some studies [10, 16] showed the correlation was good.…”
Section: Introductionmentioning
confidence: 99%